Giannozzo Manetti's New Testament : translation theory and practice in fifteenth-century Italy - Haan, Annet den, 1985- (Brill's studies in intellectual history, 2016)
In 'Giannozzo Manetti's New Testament' Annet den Haan analyses the Latin translation of the Greek New Testament made by the fifteenth-century humanist Giannozzo Manetti (1396-1459). The book includes the first edition of Manetti's text. Manetti's translation was the first since Jerome's Vulgate, and it predates Erasmus' 'Novum Instrumentum' by half a century. Written at the Vatican court in the 1450s, it is a unique example of humanist philology applied to the sacred text in the pre-Reformation era. Den Haan argues that Manetti's translation was influenced by Valla's 'Annotationes', and compares Manetti's translation method with his treatise on correct translation, 'Apologeticus' (1458).